Developement of automatic cloth folding machine using LDR sensor / Muhammad Iddin Harith Zulfakri, Muhammad Fariq Ghazali and Muhammad Izzuddin Sardi - Zulfakri, Muhammad Iddin Harith; Ghazali, Muhammad Fariq; Sardi, Muhammad Izzuddin (2017)
In this paper, the development of automatic cloth folding machine using LDR sensor is presented. This project is invented based on the problems that have been faced by most of the people usually working women who lack of time in doing their house chores, especially in folding the clothes. “Development of Automatic Cloth Folding Machine Using LDR Sensor” is an automatic motor controlled t-shirt folding machine powered by lithium battery. The aim of this project is to fold t-shirts merely by pressing a button and turned on using LDR sensor. The folding machine is fully automatic where user can place the t-shirt on the folding tray and press the button. It will then fold the t- shirt by itself. This system only uses four servo motors and LDR to control the rotation motion of the folding part. In this propose system, a servo motor is attached to the folding motion and rotates according to a program programmed by Arduino Atmega328p microcontroller. The result shows that by using this system, the time for folding clothes by human can be cut down in half compared to conventional method.